Selecting the Best Theory to Explain the Formation of Different Universities Based on Sadra’s Philosophy - Babakhan, Alireza; Shafia, Mohammad Ali; Rafiei Atani, Ata Allah; Aliahmadi, Alireza (International Journal of Economics, Management and Accounting, 2024)
In recent years, the role of universities in the development of societies has increased. In Iran, as in other countries, universities have made changes to their programs, but it still seems they need some new policies to strengthen the impact of universities on the development of society. While explaining the reasons for the formation of existing universities at the international level, this article attempts to use the framework of Sadra's philosophy to present a new type of university called “wisdom-oriented” university. This university activates the four functions as follows: Graduate education, Development of technology and technical knowledge, Problem-solving and communicating with society (such as industry, government institutions, etc.), and Producing and disseminating of knowledge content. If the wisdom-based university is formed and institutionalized, the following characteristics could be expected: “Avoidance of particularity”, “attention to comprehensiveness and gradual shift to specialization”, “scientific moderation and attention to wisdom”, “fostering creativity, production and accumulation of knowledge content”, “duty-oriented interaction with society”, “unbounded activity”, “continuous effort to come closer to God” and “optimal use of science and technology.”